2020
DOI: 10.7759/cureus.10840
|View full text |Cite
|
Sign up to set email alerts
|

Role of Vitamin D Supplementation in Heart Failure Patients With Vitamin D Deficiency and Its Effects on Clinical Outcomes: A Literature Review

Abstract: Vitamin D deficiency has become a global pandemic affecting approximately one billion people worldwide. Much attention has been paid to the association of low serum 25-hydroxyvitamin D (25(OH)D) levels and various chronic diseases, especially heart failure (HF). A clear role of vitamin D deficiency has been established, with increased mortality and morbidity in heart failures. However, previous randomized control trials have failed to show improvement in clinical outcomes with calciferol supplementation in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…[22] Finally, low vitamin D level leads to increase parathyroid hormone level, subsequently causing left ventricular hypertrophy and affecting systolic function. [23] The current meta-analysis suggested that HF patients with low serum 25-hydroxyvitamin D level should be received closely monitored and intensive treatment. HF patients with low 25-hydroxyvitamin D level may be potentially benefited by vitamin D supplementation.…”
Section: Discussionmentioning
confidence: 91%
“…[22] Finally, low vitamin D level leads to increase parathyroid hormone level, subsequently causing left ventricular hypertrophy and affecting systolic function. [23] The current meta-analysis suggested that HF patients with low serum 25-hydroxyvitamin D level should be received closely monitored and intensive treatment. HF patients with low 25-hydroxyvitamin D level may be potentially benefited by vitamin D supplementation.…”
Section: Discussionmentioning
confidence: 91%
“…2 Vitamin D plays a role in regulation of the renin-angiotensin-aldosterone system; a deficiency can result in uninhibited renin-angiotensin-aldosterone system activation, causing worsening heart failure. 3 Selenium deficiency is uncommon in Canadian children. Low soil micronutrients in parts of the world can result in selenium deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…4 Micronutrient replacement within a time-sensitive period has been shown to prevent myocyte death and restore overall heart function. 3 Refugee children present with failure to thrive and micronutrient deficiencies due to poor nutrition. 6 Infants with heart failure have an increased metabolic demand and have significantly higher caloric intake requirements.…”
Section: Discussionmentioning
confidence: 99%
“…2 In a study, it was revealed that the risk of hospitalization and mortality increased due to vitamin D deficiency in patients with heart failure. 3 The effects of vitamin D deficiency on atrial fibrillation (AF) are explained by direct effects on atrial tissue and indirect effects on cardiovascular risk factors. 4 Postoperative atrial fibrillation (PoAF) is an important problem that increases mortality and morbidity rates after cardiac surgery operations.…”
Section: Commentarymentioning
confidence: 99%
“…Apart from all these, its effects on atherosclerotic cardiovascular diseases, stroke, and cardiac remodeling have also been shown 2 . In a study, it was revealed that the risk of hospitalization and mortality increased due to vitamin D deficiency in patients with heart failure 3 . The effects of vitamin D deficiency on atrial fibrillation (AF) are explained by direct effects on atrial tissue and indirect effects on cardiovascular risk factors 4 …”
Section: Commentarymentioning
confidence: 99%